2021
DOI: 10.1080/13636820.2021.1895873
|View full text |Cite
|
Sign up to set email alerts
|

A case study of a Turkish vocational high school, and the challenges for teachers

Abstract: This case study reports on challenges and professional perspectives of vocational high school teachers working in a socially disadvantaged in rural Turkey. The data were gathered from 14 participants, including teachers, administrators and counsellor through individual and focus group interviews and classroom observations. The analysis found that students in Turkish vocational high schools are negatively positioned, this was evidenced in poor student engagement and the struggles of classroom management experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Industrial class management policies in schools are carried out by maintaining good communication with all stakeholders; bureaucratic structure tailored to industry needs; qualified human resources; internal training of trainers and industry guest teachers; disposition or attitude of policy implementers, according to a letter from the industry. In line with previous research, it implies that there is a need for social justice advocacy for vocational high school students by training teachers and improving the system with policy development (Ayaz & Özdemir, 2023). Industry classroom policies to promote early adjustment so that students arrive at companies better prepared and can allocate more time for productive tasks (de Amesti et al, 2023).…”
Section: Policies Regulations and Policies In Industrial Classes In I...supporting
confidence: 53%
“…Industrial class management policies in schools are carried out by maintaining good communication with all stakeholders; bureaucratic structure tailored to industry needs; qualified human resources; internal training of trainers and industry guest teachers; disposition or attitude of policy implementers, according to a letter from the industry. In line with previous research, it implies that there is a need for social justice advocacy for vocational high school students by training teachers and improving the system with policy development (Ayaz & Özdemir, 2023). Industry classroom policies to promote early adjustment so that students arrive at companies better prepared and can allocate more time for productive tasks (de Amesti et al, 2023).…”
Section: Policies Regulations and Policies In Industrial Classes In I...supporting
confidence: 53%
“…Since it is thought that the self and identity development of individuals continue during adolescence, their feelings and thoughts about the future may change irregularly (Steinberg, 2007). In addition, lack of interest and motivation and low academic achievement (Ayaz & Karacan-Özdemir, 2021) are among the problems experienced by TVET students. These problems can lead to situations such as students' random answers to items due to loss of interest and motivation (responding to one item at the highest level while giving the lowest response to the other and repeating it for all scales), answering without understanding what they have read, giving quick answers to finish quickly, which will reduce reliability.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…Çelebi and Deliktaş (2017) emphasized that there are many problem areas such as low economic opportunities of students, low industry-school cooperation, low job opportunities for graduate students. In their study, Ayaz and Karacan-Özdemir (2021) reported that the problems related to students are lack of interest and motivation, low self-efficacy belief, low academic achievement, and sociocultural structure (for example, the disadvantaged conditions of the region where students live, low expectations for the future of the students from their environment). Similarly, in their study, Yeşil and Tunç (2020) showed that low academic achievement, limited options, and disadvantaged conditions were among the problems of students.…”
Section: Introductionmentioning
confidence: 99%
“…The challenge for Vocational Schools is the change in skills needed by industry, especially what is happening in the 21st century (Ayaz & Karacan Özdemir, 2021). The 21st century is a century of change which is also known as the century of information technology, globalization, industrial revolution 4.0, and so on.…”
Section: Introductionmentioning
confidence: 99%